Методичний підхід до вивчення ефективності управління оновленням капіталу будівельних підприємств - Гойко, А. Ф.; Сорокіна, Л. В. (Ways to Improve Construction Efficiency, 2013)
Methodical approach to determine the effectiveness of the financial mechanism of the building enterprises that invest in technological innovation. The basis of the approach, which allows to determine the adequacy of cash flows, put the cluster analysis using the k-means and elements of the theory of fuzzy sets.